The GATT/WTO welfare effects: 1950–2015 - CHANG, Pao-Li (Institutional Knowledge at Singapore Management University, 2022)
This paper evaluates the welfare eﬀects of GATT/WTO-induced reductions in tariﬀs, vari-able and ﬁxed trade costs, based on identiﬁed direct eﬀects of membership indicators on trade ﬂows via nonparametric matching estimations. The identiﬁcation does not require the use of tariﬀ data, which permits a comprehensive evaluation of the welfare impact of GATT/WTO for a long panel since its inception (1950–2015) of as many as 180 economies. The results indicate substantial (but highly dispersed) welfare gains across members of diﬀerent development stages and increasing welfare losses of nonmembers in later decades by staying outside the system. An extensive set of robustness checks with respect to model speciﬁcations, parameter values, and matching estimations are provided. We also characterize the eﬀects of GATT/WTO on cross-country income disparity, its complementarity with preferential trade agreements, and the welfare impacts of China’s WTO entry on the other economies.